Evaluasi Kesiapan Calon Mahasiswa Terhadap Teknologi Sistem Pendaftaran Online Dengan Pendekatan Technology Readiness Index - Naufal Fikri, R. Adlian; Permana, Inggih; Nur Salisah, Febi; Saputra, Eki; Marsal, Arif (Journal of Informatics, Electrical and Electronics Engineering, 2025)
This study aims to evaluate the technological readiness of prospective students in using the online registration system facilitated by LPSDM Aparatur, employing the Technology Readiness Index (TRI) approach. TRI comprises four key dimensions: Optimism, Innovativeness, Discomfort, and Insecurity, which measure an individual's readiness to adopt new technologies. The research objects are newly enrolled students who registered through the online system provided by LPSDM Aparatur at two partner universities: Universitas Ekasakti and Universitas Nurdin Hamzah. The research uses a descriptive quantitative method with a proportional stratified sampling technique. The sample size of 43 respondents—28 from Universitas Ekasakti and 15 from Universitas Nurdin Hamzah—was determined using the Slovin formula. Data were collected using Likert scale-based questionnaires and analyzed with SPSS version 20 through validity and reliability tests, as well as descriptive statistical analysis. The findings reveal that the overall level of technological readiness is high, with a TRI score of 4.49 for Universitas Ekasakti and 4.36 for Universitas Nurdin Hamzah, both exceeding the threshold for the “high” category (>3.51). Students from Universitas Ekasakti scored highest in the Innovativeness dimension (1.11), indicating a strong tendency to try and adopt new technologies. In contrast, students from Universitas Nurdin Hamzah scored relatively high in negative dimensions, namely Insecurity (1.162) and Discomfort (1.08), suggesting psychological barriers and discomfort in using the online registration system. The study recommends training, socialization, and system simplification to ensure inclusivity and accessibility for users from diverse backgrounds. Academically, this research expands the application of TRI in the context of online-based rural education. Practically, it offers a foundation for LPSDM to develop targeted training and outreach strategies for students in regions with lower readiness levels